Silicon-based nano flower-shaped catalyst composite material as well as preparation method and application thereof
By installing a dopamine coating on the aluminum silicate nanoflower substrate of the silicon-based nanoflower-shaped catalyst composite material and supporting metal nanoparticles, the problem that existing catalysts are difficult to load a large amount of metal cations is solved, and an efficient carbon dioxide hydrogenation and methanol production reaction is achieved.
Patent Information
- Application Number
- CN202411858119.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing reaction catalysts for hydrogenation of carbon dioxide to methanol have poor conversion and selectivity, and it is difficult to load a large number of metal cations, which limits the development of this technology.
Design a silicon-based nanoflower-like catalyst composite material to achieve efficient metal cation capture and catalytic activity by providing dopamine coating and/or polydopamine coating on an aluminum silicate nanoflower substrate.
The loading of nanometal particles in the catalyst was increased, the conversion rate and selectivity of the hydrogenation of carbon dioxide to methanol was significantly improved, and excellent catalytic activity was demonstrated.
Smart Images

Figure CN119869534A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a preparation method and application of a silicon-based nano flower-shaped catalyst composite material. Background Art
[0002] Carbon dioxide is the main greenhouse gas, and the increasing carbon dioxide content in the atmosphere has caused a series of environmental problems. In recent years, due to the increasingly serious global greenhouse effect, scientists have been committed to finding effective ways to convert carbon dioxide to reduce greenhouse gas emissions and explore renewable energy to replace traditional petroleum fuels. Methanol is the simplest saturated monohydric alcohol. As a basic organic chemical raw material, its consumption is second only to ethylene, propylene and benzene. It is mainly used in plastics, fine chemicals, petrochemicals and other fields. At the same time, methanol is also a new type of clean energy. Due to its good anti-knock property and high octane number, it can be used as a fuel.
[0003] Dopamine is a promising nitrogen-containing nanomaterial precursor with the advantages of biocompatibility, modifiability, and strong adhesion. Its excellent adhesion properties enable the dopamine coating to be loaded on almost any substrate. The large amount of ~NH and ~NH2 on it provides more active sites for metal cations and can better capture metal cations, thereby showing excellent activation performance. Therefore, it is a method that can easily change the metal composition of the catalyst.
[0004] Carbon dioxide hydrogenation to methanol, by converting waste carbon dioxide to reduce greenhouse gas emissions, and converting it into useful fuels and chemical raw materials, not only alleviates the environmental problems caused by greenhouse gas carbon dioxide, but also reduces people's dependence on non-renewable fossil resources, which is of great significance to solving energy and environmental problems. In this reaction, hydrogen is used as a reducing agent to reduce carbon dioxide to methanol, and the selection of catalyst plays a vital role in the rate and selectivity of the reaction. At present, the reaction catalyst of carbon dioxide hydrogenation to methanol has poor conversion rate and selectivity, and the common catalyst base material is poor, and it is difficult to load a large amount of metal cations, thereby limiting the development of this technology. Therefore, in order to overcome this problem, it is necessary to design a high-efficiency catalyst that can load a large amount of metal cations. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a method for preparing and applying a silicon-based nanoflower-like catalyst composite material, wherein the special nanoflower-like morphology of the catalyst has the characteristics of highly open space that can effectively utilize the active sites, and the dopamine coating can be loaded on any substrate and is rich in a large amount of ~NH and ~NH2, which can be used to enhance the capture of metal cations, change the metal composition of the catalyst, and show excellent catalytic activity.
[0006] The present invention discloses a silicon-based nano-flower-shaped catalyst composite material, which comprises an aluminum silicate nano-flower substrate and metal nano-particles attached to the inner and outer surfaces of the aluminum silicate nano-flower substrate. Before loading the metal nano-particles, a coating is arranged on the aluminum silicate nano-flower substrate, and the coating is a dopamine coating and / or a polydopamine coating.
[0007] The invention discloses a silicon-based nano-flower-shaped catalyst composite material, which has an aluminum silicate nano-flower substrate and has fibrous open pores. After metal nano-particles are attached, the substrate still has fibrous open pores.
[0008] The present invention discloses a silicon-based nano-flower-shaped catalyst composite material, wherein the amount of metal nanoparticles attached is more than 7.5% of the total mass of the composite material, preferably 10-25%. The design scheme of the present invention can maximize the loading amount of nano-metal particles in the catalyst.
[0009] The present invention discloses a silicon-based nano-flower-shaped catalyst composite material, wherein the material of the metal nanoparticles is selected from at least one of copper, zinc, nickel, platinum, iron, silver, gold and platinum. Preferably, at least two of the materials are selected from copper, zinc, nickel, platinum, iron, silver, gold and platinum. More preferably, copper and zinc are selected. As a further preferred embodiment, the mass ratio of copper to zinc is 10-12:7-8.
[0010] The present invention provides a method for preparing a silicon-based nano-flower-shaped catalyst composite material, comprising the following steps: Step 1: water-soluble aluminum salt, benzoic acid, and polyvinyl pyrrolidone are dissolved in solvent A, and then a hydrothermal reaction is carried out. The obtained precipitate is washed and dried to obtain an aluminum-containing organic metal framework; the solvent A is composed of ethanol, acetone, nitric acid, and water; Step 2: calcining the product obtained in step 1, adding the product and urea to solvent B and mixing them evenly, and then adding organic silicate and performing a hydrothermal reaction; the obtained product is washed and dried to obtain aluminum silicate nanoflowers; the solvent B is composed of methanol and water; Step 3: Disperse the aluminum silicate nanoflowers produced in step 2 in a dispersion, add dopamine according to a set ratio, mix and stir, let stand, wash with water and dry; obtain an aluminum silicate nanoflower substrate loaded with dopamine; the dispersion is selected from at least one of tris(hydroxymethylaminomethane) buffer, phosphate buffer, citric acid-sodium citrate buffer, and glycine-hydrochloric acid buffer; Step 4: The product in step 3 is mixed with water and a water-soluble metal salt and stirred evenly. After solid-liquid separation, the solid is calcined, and after calcination, it is reduced to obtain a silicon-based nanoflower-like catalyst composite material.
[0011] The preparation method of the invention is simple and easy to implement, and the conditions are mild.
[0012] In step 1 of the present invention, the water-soluble aluminum salt is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum acetate, aluminum oxalate, and aluminum chloride, preferably aluminum nitrate. When used in industry, a hydrate of aluminum nitrate, such as aluminum nitrate nonahydrate, can be selected.
[0013] In step 1 of the present invention, the benzoic acid is selected from at least one of trimesic acid, p-benzoic acid, o-benzoic acid, and iso-benzoic acid, preferably trimesic acid.
[0014] As a preferred solution, aluminum nitrate nonahydrate, trimesic acid, and polyvinyl pyrrolidone are dissolved in solvent A, and then subjected to a hydrothermal reaction, and the precipitate is washed three times with ethanol and centrifuged and dried. Furthermore, in step 1, the mass ratio of aluminum nitrate nonahydrate, trimesic acid, and polyvinyl pyrrolidone is 2-3:1-2:6-7, and the volume ratio of ethanol, acetone, nitric acid with a concentration of 32.5wt%, and water is 6-9:6-9:1:3.
[0015] Furthermore, the temperature of the hydrothermal reaction in step 1 is 140-160°C, preferably 148-152°C, and the time is 40-50 h. In the present invention, the long-term hydrothermal reaction at 140-160°C is beneficial to increase its surface area, which provides the necessary conditions for the subsequent loading of more and finer nano-metal particles.
[0016] Furthermore, in step 2, after the product obtained in step 1 is calcined, it is added to solvent B at a mass ratio of 1 to 2:3 to 4 with urea; the molar ratio of methanol to water in solvent B is 2 to 3:1.
[0017] Furthermore, in step 2, 3-5 mg of urea is mixed with 0.8-1.2 ml of solvent B.
[0018] Furthermore, in step 2, the organic silicate is selected from at least one of tetraethyl orthosilicate, methyl silicate and phenyl silicate. The mass ratio of the organic silicate to the solvent B is 50:1 to 55:1.
[0019] Furthermore, the reaction temperature of the hydrothermal reaction in step 2 is 160-220°C, preferably 185-195°C, and the reaction time is 14-16 h. In industrial applications, after the hydrothermal reaction is completed, the obtained product aluminum silicate nanoflowers are washed with ethanol at least twice and dried. The drying method includes centrifugal drying.
[0020] Preferably, the aluminum silicate nanoflowers produced in step 2 are dispersed in hydroxymethylaminomethane buffer, and dopamine is dispersed in tris(hydroxymethylaminomethane) buffer. The mixture is stirred and allowed to stand overnight, then washed with water at least twice and centrifuged to dry.
[0021] Furthermore, in step 3, the solid-liquid ratio of aluminum silicate nanoflowers to the dispersion is 4-6 mg: 2-3 mL, and the solid-liquid ratio of dopamine to the dispersion is 40-60 mg: 1-3 mL.
[0022] Furthermore, the concentration of tris(hydroxymethyl)aminomethane in the dispersion of step 3 is 45-55 mmol / L, preferably 48-52 mmol / L, and the preferred pH value is 8-9. In industrial applications, the real-time temperature of step (3) is 0-40°C, including 20-25°C.
[0023] In step 4, the water-soluble metal salt is selected from at least one of copper nitrate, copper acetate, copper sulfate, copper oxalate, copper chloride, zinc acetate, zinc sulfate, zinc nitrate, zinc oxalate, and zinc chloride.
[0024] Furthermore, in step 4, the mass ratio of the aluminum silicate nanoflower substrate loaded with dopamine to copper nitrate nonahydrate and zinc acetate is 1:1-3:9-11, and the solid-liquid ratio of the aluminum silicate nanoflower substrate loaded with dopamine to water is 20 mg:1-3 mL.
[0025] Furthermore, in step 4, the calcination temperature is 330-370° C., and the calcination time is 2-3 h.
[0026] Furthermore, in step 4, the reduction temperature is 280-320° C. and the time is 2-6 hours.
[0027] Another object of the present invention is to provide an application method of a catalyst for preparing methanol by hydrogenation of carbon dioxide, comprising the following steps: Step 1 A fixed bed reactor is used to load a silicon-based nano-flower-shaped catalyst composite material or a silicon-based nano-flower-shaped catalyst composite material precursor; Step 2 After completing step 1, a mixture of carbon dioxide and hydrogen is introduced for reaction. The reaction temperature is 200-280° C., the reaction pressure is 2-5 MPa, preferably 3 MPa, and the volume ratio of carbon dioxide to hydrogen is 1:3.
[0028] In industrial applications, in order to improve the activity of the catalyst, generally after calcination in step (4), a copper-silicon catalyst precursor (i.e., a precursor of a silicon-based nanoflower-shaped catalyst composite material) is obtained, which is collected and, when used, a fixed bed reactor is used, the copper-silicon catalyst precursor is loaded, and a programmed temperature is raised in a hydrogen atmosphere, and the mixture is reduced at 280-320°C for 2-6 hours and then cooled to the reaction temperature; then a mixture of carbon dioxide and hydrogen is introduced for reaction, the reaction temperature is 200-280°C, the reaction pressure is 2-5MPa, preferably 3MPa, wherein the volume ratio of carbon dioxide to hydrogen is 1:3; and the target product, methanol, is obtained.
[0029] The catalyst of the present invention presents a special nanoflower-like morphology with fibrous open pores, highly open space and effective utilization of active sites, etc. Compared with solid nanoparticles (NPs), it promotes the dispersion of active metal species components, which can effectively reduce the electron and mass transfer paths and accelerate the catalytic process.
[0030] The advantages and positive effects of the present invention are: The catalyst of the present invention presents a special nano-flower-like morphology and has fibrous open pores, which promotes the dispersion of active metal species components and improves the catalytic reaction efficiency in the production of methanol by hydrogenation of carbon dioxide.
[0031] 2. The catalyst of the present invention utilizes the characteristics that the dopamine coating can be loaded on any substrate and is rich in ~NH and ~NH2, providing a large number of active sites for adsorbing metal cations and changing the metal composition of the catalyst. Compared with the traditional catalyst substrate material, which is poor and difficult to load a large number of metal cations, it achieves excellent performance of high conversion rate and high selectivity.
[0032] 3. The catalyst of the present invention is used in the production of methanol by hydrogenation of carbon dioxide, which improves the catalytic efficiency and has an excellent catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is an electron microscope image of the silicon-based nanoflower catalyst substrate obtained in Example 1; Figure 2 This is an electron microscope image of the silicon-based nanoflower catalyst substrate after dopamine modification in Example 1; Figure 3 This is an electron microscope image of the copper-zinc supported nanoflower catalyst obtained in Example 1; Figure 4 This is the electron microscope image of sample 2 obtained in comparative example 1. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with specific embodiments, but is by no means intended to limit the present invention. Features such as preparation methods, materials, structures or composition ratios not explicitly described in this technical solution are considered to be common technical features disclosed in the prior art.
[0035] The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several modifications and improvements may be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0036] The practice of the present invention may employ conventional techniques of polymer chemistry within the skill of the art. In the following examples, efforts have been made to ensure accuracy with respect to numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be accounted for.
[0037] In this embodiment, all reagents used are commercially available reagents.
[0038] Embodiment 1: This embodiment provides a method for preparing a silicon-based nano-flower-shaped catalyst composite material and its application, comprising the following steps: Step 1: 2875 mg aluminum nitrate nonahydrate, 1000 mg trimesic acid, and 6375 mg polyvinyl pyrrolidone were dissolved in a mixture of 93.75 mL ethanol, 93.75 mL acetone, 12.5 mL 32.5% nitric acid, and 37.5 mL water, and the mixture was transferred to a Teflon-lined reactor for hydrothermal reaction precipitation at 150 ° C for 45 hours, and the precipitate was washed three times with ethanol and centrifuged to obtain MIL-96 (Al) nanoparticles; Step 2: 40 mg of MIL-96 (Al) nanoparticles were calcined in a tube furnace at 500 ° C in air atmosphere for 1 h, and then fully ultrasonically dispersed with 120 mg of urea in a mixture of 20 mL of methanol and 10 mL of deionized water. Then, a mixed solution of tetraethyl orthosilicate and methanol in a mixing ratio of 1:10 was added and mixed. The mixture was transferred to a 190 ° C autoclave for hydrothermal reaction for 15 h. The precipitate was washed three times with ethanol and centrifuged to obtain aluminum silicate nanoparticles (such as Figure 1 shown); Step 3: Disperse 50 mg of aluminum silicate nanoflower particles in step 2 in 30 mL of 50 mM, pH 8.5 tris(hydroxymethylaminomethane) buffer, disperse 50 mg of dopamine in 1 mL of tris(hydroxymethylaminomethane) buffer, mix and stir, let stand overnight, wash twice with water and centrifuge to obtain dopamine-modified aluminum silicate nanoflower particles (such as Figure 2 shown); Step 4: 100 mg of dopamine-modified aluminum silicate nanoflower particles in step 3 were mixed with 5 mL of water, 120 mg of 0.1 M copper nitrate, and 1098 mg of 1 M zinc acetate, washed once with water, centrifuged and dried, and placed in a muffle furnace and calcined at 350° C. for 2 h at a rate of 2° C. / min to obtain a copper-zinc-supported nanoflower catalyst, recorded as sample 1. The actual loading of metallic copper and metallic zinc on the catalyst surface was detected by ICP.
[0039] Step 5: Reduce the catalyst in a hydrogen atmosphere at 300°C for 4 h and set aside for later use (e.g. Figure 3 as shown).
[0040] Step 6: 200 mg of the reduced catalyst was loaded into a fixed bed reactor, and a mixture of carbon dioxide and hydrogen was introduced for reaction at a reaction temperature of 200-280°C and a reaction pressure of 3 MPa, wherein the volume ratio of carbon dioxide to hydrogen was 1:3. The tail gas composition and concentration were detected by gas chromatography, and the conversion rate of carbon dioxide and the selectivity of methanol were calculated.
[0041] like Figure 1 As shown, the catalyst obtained in step 2 of this embodiment exhibits a special nanoflower morphology with fibrous open pores, which promotes the dispersion of active metal species components. Figure 2 As shown in FIG. 3 , after dopamine modification in step 3, the surface of the nanoflower is covered with a thin layer of functionalized dopamine film, which can enhance the anchoring effect of metal cations on the catalyst surface. Figure 3 As shown in Table 1, due to the unique pore structure of the nanoflower and the strong adsorption of the dopamine layer, the metal copper and metal zinc nanoparticles are evenly distributed on the catalyst surface and in the pore structure. As shown in Table 1, the loading of metal copper and metal zinc in sample 1 reaches 12.0% and 8.0%, respectively. As shown in Table 1, the carbon dioxide conversion rate and methanol selectivity of sample 1 reach 17% and 16%, respectively.
[0042] Comparative Example 1: This comparative example provides a dopamine-modified MIL-96 (Al) nanoparticle substrate material for adsorbing copper and zinc cations. The difference from Example 1 is that step 2 is not performed, that is, the MIL-96 (Al) nanocrystal particles obtained in step 1 are not expanded into nanoflowers, which is recorded as sample 2. Figure 4 .
[0043] The metal loadings of the metal copper and metal zinc in the comparative example sample 2 are only 1.0% and 0.7%, which are lower than those in the sample 1. The carbon dioxide conversion rate and methanol selectivity of the comparative example sample 2 are 2.1% and 3.0%, respectively, which are lower than those in the sample 1.
[0044] Comparative Example 2: This comparative example provides a common nanoflower-shaped catalyst base material for adsorbing copper and zinc cations. The difference from Example 1 is that step 3 is not implemented, that is, the aluminum silicate nanoflower particles obtained in step 2 are not functionalized with dopamine, and is recorded as sample 3.
[0045] As shown in Table 1, the metal loadings of copper and zinc in comparative example sample 3 are only 2.0% and 2.0%, respectively, which are lower than those in sample 1. The carbon dioxide conversion rate and methanol selectivity of comparative example sample 3 are 4.5% and 4%, respectively, which are lower than those in sample 1.
[0046] Comparative Example 3: This comparative example provides a dopamine-modified MIL-96 (Al) nanoparticle base material for adsorbing copper and zinc cations. The difference from Example 1 is that in step 3, 50 mg of aluminum silicate nanoflower particles are dispersed in 30 mL of 50 mM, pH 8.5 tris(hydroxymethylaminomethane) buffer, and 15 mg of dopamine is dispersed in 1 mL of tris(hydroxymethylaminomethane) buffer. The mixture is stirred and allowed to stand overnight, then washed twice with water and centrifuged to obtain dopamine-modified aluminum silicate nanoflower particles, which are recorded as sample 4.
[0047] As shown in Table 1, the metal copper and metal zinc loadings of the comparative example sample 4 are only 4.5% and 3.4%, which are lower than those of the sample 1. The carbon dioxide conversion rate and methanol selectivity of the comparative example sample 2 are 2.1% and 3.0%, respectively, which are lower than those of the sample 1.
[0048] Example 2: This example provides a dopamine-modified MIL-96 (Al) nanoparticle base material for adsorbing copper and zinc cations. The difference from Example 1 is that in step 3, 50 mg of aluminum silicate nanoflower particles are dispersed in 30 mL of 50 mM, pH 8.5 tris(hydroxymethylaminomethane) buffer, and 40 mg of dopamine is dispersed in 1 mL of tris(hydroxymethylaminomethane) buffer. The mixture is stirred and allowed to stand overnight, then washed twice with water and centrifuged to obtain dopamine-modified aluminum silicate nanoflower particles, which are recorded as sample 5.
[0049] As shown in Table 1, the metal copper and metal zinc loadings of the comparative example sample 5 are only 10.0% and 7.0%, which are lower than those of the sample 1. The carbon dioxide conversion rate and methanol selectivity of the comparative example sample 5 are 14.0% and 13.0%, respectively, which are lower than those of the sample 1.
[0050] Example 3: This example provides a dopamine-modified MIL-96 (Al) nanoparticle substrate material for adsorbing copper and zinc cations. The difference from Example 1 is that in step 4, 100 mg of dopamine-modified aluminum silicate nanoflower particles are mixed with 5 mL of water and 120 mg of copper nitrate, washed once, centrifuged and dried, placed in a muffle furnace and calcined at 350 ° C for 2 h at a rate of 2 ° C / min to obtain a copper-supported nanoflower catalyst, and the actual amount of metal copper loaded on the catalyst surface is detected by ICP. Recorded as sample 6.
[0051] As shown in Table 1, the copper metal loading of the comparative example sample 6 is 10.2%, which is lower than that of the sample 1. The carbon dioxide conversion rate and methanol selectivity of the comparative example sample 6 are 6.4% and 5.0%, respectively, which are lower than that of the sample 1.
[0052] Comparative Example 4: This comparative example provides a dopamine-modified MIL-96 (Al) nanoparticle substrate material for adsorbing copper and zinc cations. The difference from Example 1 is that in step 4, 100 mg of dopamine-modified aluminum silicate nanoflower particles are mixed with 5 mL of water and 1098 mg of zinc acetate, washed once, centrifuged and dried, placed in a muffle furnace and calcined at 350 ° C for 2 h at a rate of 2 ° C / min to obtain a copper-supported nanoflower catalyst, and the actual metal zinc loading on the catalyst surface is detected by ICP. Recorded as sample 7.
[0053] As shown in Table 1, the metal zinc loading of the comparative example sample 7 is 2.1%, which is lower than that of the sample 1. The carbon dioxide conversion rate and methanol selectivity of the comparative example sample 7 are 1.7% and 0.9%, respectively, which are lower than that of the sample 1.
[0054] Example 4: This example provides a dopamine-modified MIL-96 (Al) nanoparticle substrate material for adsorbing copper and zinc cations. The difference from Example 1 is that in step 4, 100 mg of dopamine-modified aluminum silicate nanoflower particles are mixed with 5 mL of water, 120 mg of copper nitrate, and 590 mg of zinc acetate, washed once, centrifuged and dried, placed in a muffle furnace and calcined at 350 ° C for 2 h at a rate of 2 ° C / min to obtain a copper-supported nanoflower catalyst, and the actual metal copper and metal zinc loading on the catalyst surface are detected by ICP. Recorded as sample 8.
[0055] As shown in Table 1, the metal copper and metal zinc loadings of the comparative example sample 8 were 10.6% and 2.5%, respectively, which were lower than those of the sample 1. The carbon dioxide conversion rate and methanol selectivity of the comparative example sample 8 were 9.0% and 9.0%, respectively, which were lower than those of the sample 1.
[0056] The results show that the copper-zinc-loaded silicon-based nanoflower catalyst preparation process of the invention is real and effective, and the catalyst can be used for catalytic production of methanol by hydrogenation of carbon dioxide. Comparative Examples 1 and 2 can prove that nanoflower structure and dopamine functionalization are both essential conditions in the catalyst. Comparative Examples 3 and 4 can prove that the higher the dopamine content, the more it can promote the loading of metallic copper and metallic zinc. Comparative Examples 5, 6 and 7 can prove that copper nitrate and zinc acetate promote each other on the metal loading, and a certain proportion of copper nitrate and zinc acetate has an optimization effect on the metal ion loading.
[0057]
[0058] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned description of the embodiments for the convenience of ordinary technicians in the technical field to understand and use the invention. It is obvious that those familiar with the technology in the field can easily make various modifications to these embodiments and apply the general principles described here to other embodiments without creative work. Therefore, the present invention is not limited to the above-mentioned embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A silicon-based nano-flower-shaped catalyst composite material, characterized in that: The silicon-based nanoflower-shaped catalyst composite material comprises an aluminum silicate nanoflower substrate and metal nanoparticles attached to the inner and outer surfaces of the aluminum silicate nanoflower substrate. Before loading the metal nanoparticles, a coating is provided on the aluminum silicate nanoflower substrate, and the coating is a dopamine coating and / or a polydopamine coating.
2. The silicon-based nano-flower-shaped catalyst composite material according to claim 1, characterized in that: The aluminum silicate nanoflower substrate has fibrous open pores, and after the metal nanoparticles are attached, it still has fibrous open pores.
3. The silicon-based nanoflower-shaped catalyst composite material according to claim 1, characterized in that: The amount of metal nanoparticles attached is more than 7.5% of the total mass of the composite material; The material of the metal nanoparticles is at least one selected from copper, zinc, nickel, platinum, iron, silver, gold, and platinum.
4. A method for preparing the silicon-based nanoflower-shaped catalyst composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: water-soluble aluminum salt, benzoic acid, and polyvinyl pyrrolidone are dissolved in solvent A, and then a hydrothermal reaction is carried out. The obtained precipitate is washed and dried to obtain an aluminum-containing organic metal framework; the solvent A is composed of ethanol, acetone, nitric acid, and water; Step 2: calcining the product obtained in step 1, adding the product and urea to solvent B and mixing them evenly, and then adding organic silicate and performing a hydrothermal reaction; the obtained product is washed and dried to obtain aluminum silicate nanoflowers; the solvent B is composed of methanol and water; Step 3: Disperse the aluminum silicate nanoflowers produced in step 2 in a dispersion, add dopamine according to a set ratio, mix and stir, let stand, then wash with water and dry; A dopamine-loaded aluminum silicate nanoflower substrate is obtained; the dispersion liquid is selected from at least one of tris(hydroxymethylaminomethane) buffer, phosphate buffer, citric acid-sodium citrate buffer, and glycine-hydrochloric acid buffer; Step 4: The product in step 3 is mixed with water and a water-soluble metal salt and stirred evenly. After solid-liquid separation, the solid is calcined, and after calcination, it is reduced to obtain a silicon-based nanoflower-like catalyst composite material.
5. The method for preparing a silicon-based nano-flower-shaped catalyst composite material according to claim 4, characterized in that: In step 1, the water-soluble aluminum salt is selected from at least one of aluminum nitrate, aluminum sulfate, aluminum acetate, aluminum oxalate, and aluminum chloride; In step 1, the benzoic acid is selected from at least one of trimesic acid, p-benzoic acid, o-benzoic acid, and isobenzoic acid.
6. The method for preparing a silicon-based nanoflower-shaped catalyst composite material according to claim 5, characterized in that: Aluminum nitrate nonahydrate, trimesic acid, and polyvinyl pyrrolidone were dissolved in solvent A, and then subjected to hydrothermal reaction. The precipitate was washed three times with ethanol and centrifuged to dry. In the step 1, the mass ratio of aluminum nitrate nonahydrate, trimesic acid, and polyvinyl pyrrolidone is 2-3:1-2:6-7, and the volume ratio of ethanol, acetone, 32.5wt% nitric acid, and water is 6-9:6-9:1:3; In step 1, the hydrothermal reaction temperature is 140-160° C. and the reaction time is 40-50 h.
7. The method for preparing a silicon-based nano-flower-shaped catalyst composite material according to claim 4, characterized in that: In the step 2, after the product obtained in step 1 is calcined, it is added to solvent B at a mass ratio of 1 to 2:3 to 4 with urea; the molar ratio of methanol to water in solvent B is 2 to 3:1; In step 2, 3-5 mg of urea is mixed with 0.8-1.2 ml of solvent B; In step 2, the organic silicate is selected from at least one of tetraethyl orthosilicate, methyl silicate and phenyl silicate. The mass ratio of the organic silicate to the solvent B is 50:1 to 55:1; The temperature of the hydrothermal reaction in step 2 is 160-220° C., and the reaction time is 14-16 h.
8. The method for preparing a silicon-based nano-flower-shaped catalyst composite material according to claim 4, characterized in that: In step 3, the solid-liquid ratio of aluminum silicate nanoflowers to the dispersion is 4-6 mg: 2-3 mL, and the solid-liquid ratio of dopamine to the dispersion is 40-60 mg: 1-3 mL; The concentration of tris(hydroxymethyl)aminomethane in the dispersion of step 3 is 45-55 mmol / L, preferably 48-52 mmol / L, and the pH value thereof is 8-9.
9. The method for preparing a silicon-based nano-flower-shaped catalyst composite material according to claim 4, characterized in that: In step 4, the water-soluble metal salt is selected from at least one of copper nitrate, copper acetate, copper sulfate, copper oxalate, copper chloride, zinc acetate, zinc sulfate, zinc nitrate, zinc oxalate, and zinc chloride; In the step 4, the mass ratio of the aluminum silicate nanoflower substrate loaded with dopamine to copper nitrate nonahydrate and zinc acetate is 1:1-3:9-11, and the solid-liquid ratio of the aluminum silicate nanoflower substrate loaded with dopamine to water is 20 mg:1-3 mL; In step 4, the calcination temperature is 330-370°C and the calcination time is 2-3 hours; In step 4, the reduction temperature is 280-320° C. and the time is 2-6 hours.
10. Use of a silicon-based nano-flower-shaped catalyst composite material according to any one of claims 1 to 3, characterized in that The steps include: Step 1 A fixed bed reactor is used to load silicon-based nano-flower-like catalyst composite materials or precursors; Step 2 After completing step 1, a mixture of carbon dioxide and hydrogen is introduced for reaction at a reaction temperature of 200-280° C. and a reaction pressure of 2-5 MPa, wherein the volume ratio of carbon dioxide to hydrogen is 1:3.
Citation Information
Patent Citations
A hydrogenation catalyst, a preparing method thereof, applications of the hydrogenation catalyst and a hydrogenation reaction method
CN105435809A
Preparation method of MOF derived different-structure nanoreactor
CN114082451A
Preparation method of aluminum silicate-based nanoflower porous material
CN119430209A
Method for reducing volatile organic compounds in transesterification solutions prepared from animal and vegetable oil ingredient
KR102756955B1
Multicomponent heterogeneous catalysts for direct co2 hydrogenation to methanol
US20180273454A1